Serial platelet level index improves prediction of pulmonary hemorrhage in patients with Stenotrophomonas maltophilia respiratory infections and thrombocytopenia - Wu, Huai-Chueh Gem; Wu, Huai-Shing; Cheng, Chao-Neng; Chen, Jiann-Shiuh; Chen, Tsai-Yun; Li, Chung-I; Shen, Ching-Fen (Frontiers in Medicine, 2022)
Patients with thrombocytopenia (platelet count < 150x103 /μL) often develop pulmonary hemorrhage (PH) after Stenotrophomonas maltophilia (SM) respiratory infection, resulting in a high respiratory failure rate and increased mortality. Developing an efficient method for early prediction of PH in these patients may improve survival. This study aimed to evaluate risk factors for PH and to develop an index measuring serial platelet deficit to predict PH in patients with SM respiratory infection. Data of patients with SM respiratory infection and thrombocytopenia treated in a tertiary university hospital during 2018-2020 were retrospectively retrieved from electronic medical records and analyzed. SM respiratory infection was defined as SM isolated from sputum, endotracheal suction, or bronchial alveolar lavage plus acute respiratory symptoms. Between PH and non-PH groups, clinical characteristics, and laboratory parameters were collected and compared. The newly developed platelet dissimilarity index (d-index) was calculated by accumulating differences between the actual and the lowest normal level of platelet count in each patient at different time points. Within 1039 patients with positive SM culture, 437 cases were matched the criteria and analyzed. A total of 125 (28.6%) patients developed PH and 312 (71.4%) did not. Patients with PH had increased prothrombin time/international normalized ratio (PT/INR), lower platelet count, and higher platelet d-index. Multivariate analysis revealed that extreme thrombocytopenia (platelet count < 50x103 /μL) is a common independent risk factor for PH and mortality. The performance of platelet deficit and d-index varied between patients with different comorbidities. Performance of platelet deficit to predict PH is better in patients with hematology/oncology or liver disease (area under curve 0.705-0.757), while d-index is better in patients with sepsis/treatment and various other groups (0.711-0.816). Prolonged and extreme thrombocytopenia is a determinant risk factor for PH in patients with SM respiratory infection. Given the complexity of causes of thrombocytopenia and associated comorbidities, different strategies should be applied when assessing the risk for PH.